ANALISIS FAKTOR PREDISPOSISI DIABETES MELITUS GESTASIONAL PADA IBU HAMIL TRIMESTER III - Mira Arnita; Henniwati; Emilda (JOMIS (Journal of Midwifery Science), 2026)
Gestational diabetes mellitus is a metabolic disorder first identified during pregnancy. This condition is a pregnancy complication with a high prevalence in various countries and contributes to increased morbidity and mortality in both mothers and infants. Globally, the incidence of gestational diabetes mellitus shows an increasing trend in line with the increasing prevalence of obesity and increasing maternal age during pregnancy. Given the significant impact on maternal and fetal health, early detection of gestational diabetes mellitus, especially in the third trimester, is a crucial effort in preventing pregnancy complications. This study aims to analyze predisposing factors for gestational diabetes mellitus in pregnant women in the third trimester. This study employed a correlational analytical design with a cross-sectional approach. The study sample consisted of 20 third-trimester pregnant women who had antenatal visits at the Langsa Baro Community Health Center in May 2026. Data analysis used the Chi-Square test with the help of SPSS version 21 software. The findings resulted in a significant relationship between maternal age (p-value = 0.01), parity (p-value = 0.00), and body mass index (BMI) (p-value = 0.04) with the incidence of gestational diabetes mellitus. Therefore, maternal age, parity, and BMI can be identified as factors that correlate with the occurrence of gestational diabetes mellitus in third-trimester pregnant women.